Library Users’ Perceptions of Collection Availability in Fulfilling Information Needs at the Regional Archives and Library Office of West Sumatra Province - Cahyani, Amelia Dwi; Rahmah, Elva (Darul Yasin Al Sys, 2026)
Library collection availability is essential for fulfilling users’ information needs amid increasingly dynamic information development. This study aims to examine library users’ perceptions of collection availability at the Regional Archives and Library Office of West Sumatra Province, focusing on the relevance, quantity, currency, quality, and completeness of collections in supporting information needs. A quantitative approach with a descriptive method was employed. The population consisted of 33,184 library users, from which 100 respondents were selected through simple random sampling using the Slovin formula. Data were collected through closed-ended questionnaires based on a four-point Likert scale and supported by observation and literature review. The data were analyzed using descriptive statistical techniques through mean and grand mean calculations. The findings show that the collection availability variable obtained an average score of 2.99, categorized as good, while the information needs variable achieved an average score of 3.05, also categorized as good. Among the collection availability indicators, collection currency recorded the highest score of 3.07, whereas collection quantity obtained the lowest score of 2.82. For the information needs variable, cognitive needs achieved the highest score of 3.10. These findings indicate that the library collections are perceived as sufficiently capable of fulfilling users’ information needs, particularly in supporting learning activities, research, and knowledge development. The study concludes that collection relevance, quality, currency, and completeness play an important role in strengthening the fulfillment of users’ information needs. These findings provide practical implications for public libraries by emphasizing the need for user-oriented collection development, increased collection quantity, regular collection updates, and expanded digital information resources to improve library service quality continuously.